Assessment of the specificity of Burkholderia and Pseudomonas qPCR assays for detection of these genera in soil using 454 pyrosequencing - Bergmark, Lasse; Poulsen, Pernille Hasse Busk; Al-Soud, Waleed Abu; Norman, Anders; Hansen, Lars Hestbjerg; Sørensen, Søren Johannes (FEMS microbiology letters, 2012)
Abstract In this study, two highly specific quantitative PCR assays targeting the bacterial genera Burkholderia and Pseudomonas were developed and evaluated on soil samples. The primers were targeting different multivariate regions of the 16S rRNA gene and designed to be compatible with quantitative PCR and the high throughput 454 pyrosequencing technique. The developed assays were validated using the standard methods. All tests with the new developed assays showed very high specificity. Pyrosequencing was used for direct analysis of the PCR product and applied as a specificity measurement of the primers. The Pseudomonas primers showed a 99% primer specificity, which covered 200 different Pseudomonas sequence clusters in 0.5 g of soil. In contrast to that the same approach using the genus-specific Burkholderia primers showed only 8% primer specificity. This discrepancy in primer specificity between the normal procedures compared with pyrosequencing illustrates that the common validation procedures for quantitative PCR primers may be misleading. Our results exemplify the fact that current 16S RNA gene sequence databases might lack resolution within many taxonomic groups and emphasize the necessity for a standardized and functional primer validation protocol. A possible solution to this could be to supplement the normal verification of quantitative PCR assays with a pyrosequencing approach.